Perioperative management of a patient with bleomycin lung injury and on dabigatran treatment for retro-peritoneal lymph node dissection: A case report (Indian Journal of Case Reports, 2019)
Germ cell tumors (GCT) arise from the cells that develop into sperms or eggs. They are commonly seen in testes and ovaries. Here, we report the case of a patient with bleomycin-induced lung injury (BILI) and dabigatran therapy for prior pulmonary thromboembolism underwent retroperitoneal lymph node dissection. The patient had dyspnoea and hypoxia during chemotherapy with a thrombus in the pulmonary artery and was managed with parenteral anticoagulation followed by dabigatran. He subsequently developed BILI and recovered. Dabigatran was stopped five days prior to surgery and perioperative anticoagulation bridged with dalteparin. Intraoperatively, we used inspired oxygen <35%, lung protective ventilation, goal-directed fluid therapy and intravenous morphine infusion. Postoperatively, we performed rectus sheath block and commenced transnasal humidified rapid insufflation ventilatory exchange. The patient had an uneventful recovery.